2007
DOI: 10.1021/ac0617767
|View full text |Cite
|
Sign up to set email alerts
|

Hyphenation of Gas Chromatography to Microcoil 1H Nuclear Magnetic Resonance Spectroscopy

Abstract: Whereas the hyphenation of gas chromatography (GC) with mass spectrometry is of great importance, little is known about the coupling to nuclear magnetic resonance spectroscopy (NMR). The investigation of this technique is an attractive proposition because of the valuable information given by NMR on molecular structure. The experiments shown here are to our knowledge the first hyphenating capillary GC to microcoil NMR. In contrast to liquids, gases have rarely been investigated by NMR, mainly due to the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…Some desirable spectroscopic identification methods including nuclear magnetic resonance (NMR) are not Abbreviations: DFS, deactivated fused-silica; 1,4-DMB, 1,4-dimethoxybenzene; EO, essential oil; EPC, electronic pressure control; IS, internal standard; MDGC, multidimensional GC; prep-GC, preparative gas chromatography; TMS, tetramethylsilane; xTA, external trapping assembly readily available hyphenated directly (online) with GC, and while online GC with NMR has been little reported, Albert's group [3] showed that, provided sufficient material can be introduced into the capillary column, NMR spectra can be successfully acquired in the online GC-NMR experiment. By contrast preparative GC (prep-GC) is a viable approach that can give access to such methods.…”
Section: Introductionmentioning
confidence: 99%
“…Some desirable spectroscopic identification methods including nuclear magnetic resonance (NMR) are not Abbreviations: DFS, deactivated fused-silica; 1,4-DMB, 1,4-dimethoxybenzene; EO, essential oil; EPC, electronic pressure control; IS, internal standard; MDGC, multidimensional GC; prep-GC, preparative gas chromatography; TMS, tetramethylsilane; xTA, external trapping assembly readily available hyphenated directly (online) with GC, and while online GC with NMR has been little reported, Albert's group [3] showed that, provided sufficient material can be introduced into the capillary column, NMR spectra can be successfully acquired in the online GC-NMR experiment. By contrast preparative GC (prep-GC) is a viable approach that can give access to such methods.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, microtechniques like microcoil 1 H NMR spectroscopy are much more sensitive and allow measurements of sample amounts in the low nmol range. They can also be coupled with capillary HPLC (highperformance liquid chromatography) or GC (gas chromatography) systems [19][20][21]. The HPLC-NMR or even HPLC-NMR-MS capillary technique offers a reliable analysis of unstable, light-or air-sensitive compounds in the continuous-or stopped-flow mode, and the wasteful collection of HPLC fractions, the time-consuming removal of almost nonvolatile solvents and the risk of contamination can be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…1,15 In one of their applications they isolated 8.6 lg geraniol from a complex essential oil matrix using MDGC and recorded remarkable 1 with a 800 MHz NMR spectrometer equipped with a cryoprobe within an acquisition time of 1 hr. 15 The second direct approach was published also quite recently and demonstrated the feasibility of an online coupling of gas chromatography and NMR spectroscopy 16,17 based on earlier reports of the direct combination of packed column and NMR instrumentation. 18,19 In a recent work, the successful capillary gas chromatographic separation and online identification of the stereoisomers of E,Z-2-pentene and of E,Z-2-hexene using a Chirasil-b-Dex stationary phase and a 400 MHz NMR spectrometer equipped with a custom-built, double resonant solenoidal microprobe was described.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 In a recent work, the successful capillary gas chromatographic separation and online identification of the stereoisomers of E,Z-2-pentene and of E,Z-2-hexene using a Chirasil-b-Dex stationary phase and a 400 MHz NMR spectrometer equipped with a custom-built, double resonant solenoidal microprobe was described. 17 Both methods benefit from newer developments in the field of NMR such as microprobes 16,17,20,21 or cryoprobes [22][23][24][25] and stronger magnets, which dramatically improved the sensitivity of the relatively insensitive spectroscopic method so that the largest sample amounts, which can be separated by capillary GC are getting closer to the detection limit of NMR spectroscopy. Thus it is to be expected that many applications using a combined method of GC and NMR (offline as well as online) will emerge in the future especially if a high purity isolation is required for an unequivocal identification.…”
Section: Introductionmentioning
confidence: 99%